SYSTEM OF METROLOGICAL SUPPORT AND CONTROL OF HEALTHCARE INSTITUTIONS IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Today, due to the implementation of state programs, work is underway to ensure that healthcare in our country meets the highest international requirements and standards and to improve this system. Measures have been identified to improve the quality of training qualified personnel, build and reconstruct new treatment and prevention institutions, and equip them with modern technology and equipment. The article also analyzes the role of metrological control of diagnostic equipment used in angiography and ophthalmology. Metrological support is considered an important systemic component in ensuring the accuracy, safety and efficiency of medical equipment.